If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6 = 3x + -18 Reorder the terms: -6 + 2x = 3x + -18 Reorder the terms: -6 + 2x = -18 + 3x Solving -6 + 2x = -18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + 2x + -3x = -18 + 3x + -3x Combine like terms: 2x + -3x = -1x -6 + -1x = -18 + 3x + -3x Combine like terms: 3x + -3x = 0 -6 + -1x = -18 + 0 -6 + -1x = -18 Add '6' to each side of the equation. -6 + 6 + -1x = -18 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = -18 + 6 -1x = -18 + 6 Combine like terms: -18 + 6 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| 7(1-5n)+6(1+4n)=13 | | x=7x-78 | | -6y+18=3y-10 | | 6x^2-30x-36=0 | | C=39.18+0.50x | | 6x=-46 | | 7x-5y-35=0 | | 3x=3x-11 | | 2y-5=11-6y | | 7(x-2)+3x=16 | | 5m-14=-9 | | 6.7+1.6n=3.18 | | 3x-10=2(3x-20) | | -2a+1=9 | | 7x-98=-x+134 | | a=3y-4 | | 16-8n=-8(5n+7)+8 | | 4t+9=11t-83 | | 5x+7-2=5+x | | 2(3x+1)=2x+11 | | x-50=90+8x | | 5x+7-2=5tx | | 4n-(9-3n)=8n-1 | | 98+45=458 | | 4x+6x+40=0 | | 7ln(x+2)-8lnx= | | 3n+8(2n-6)=2+14n | | 8x+6=4x-58 | | -6x-62=-x+43 | | 50t=.25t+1000 | | -3(x-11)=12 | | -6x-62=-x+134 |